The role of people's participation, monitoring and evaluation in the successful implementation of Niger Delta Development Commission projects in selected communities in Imo State - Isidiho, Alphonsus; Sabran, Mohammad Shatar (Scottish Group, 2015)
Niger Delta Development Commission (NDDC) is a Commission set up by the Federal Government of Nigeria in 2000 by the former President Chief Olusegun Aremu Obasanjo with a mandate to appease the oil producing communities. The NDDC was formed to “facilitating the rapid, even and sustainable development of the Niger Delta into a region that is economically prosperous, socially stable, ecologically regenerative and politically peaceful” as stated in the NDDC master plan. It is in line with these directives that the commission embarked on lots of public utility projects and empowerments to actualize these set objectives. The communities still complain of inadequate basic public utilities which are supposed to be provided by NDDC. The issue of participation, monitoring and evaluation has become a global approach to most programmes and projects to ensure the success of such projects. But the issue of people’s participation, monitoring and evaluation has not been fully incorporated in most developmental projects in Nigeria. The study tries to understand the level of community participation, monitoring and evaluation in the implementation of water, electricity and road projects sponsored by the Niger Delta Development Commission (NDDC) in the selected communities of Obowo, Oguta and Ohaji/Egbema communities in Imo State Nigeria, utilizing data from both primary and secondary sources. Out of 298 participants, 63.2% said their communities were not contacted before these projects were started, while 58.6% said that the projects were not monitored and evaluated. The study concludes that there were low community participation, monitoring and evaluation in NDDC projects and if at all there were in some locations as the data shows, it was very low and insignificant. Based on the findings, the study also concludes that people’s participation is a necessary condition but not a sufficient condition in the successful implementation of some public utility projects. The study recommends that though some of the projects were successfully constructed and are operational despite the fact that there were no adequate participation, monitoring and evaluation, full involvement of the communities in NDDC projects would definitely enhance the successful implementation of these projects and help to ensure the maintenance of the approved standard and best conditions of the project practice. Key word: participation, monitoring, evaluation, Niger Delta Development Commission, projects, communities.